Diffusion-Weighted MRI and FDG-PET in Diagnosis of Endometrial Stromal Nodule - Shunsuke Maruyama; Yukiyasu Sato; Yumiko Satake; Hiroko Mise; Tomoko Kim (Case Reports in Obstetrics and Gynecology)
Preoperative differentiation of benign endometrial stromal nodule (ESN) from malignant low-grade endometrial sarcoma (LGESS) is challenging, because it requires histological evaluation of the tumor-myometrium interface, which is difficult to obtain in conventional endometrial curettage. A 72-year-old postmenopausal woman presented with 5-year history of persistent vaginal bleeding. Histological examination of the endometrial curettage specimen revealed hyperplasia of apparently normal endometrial stromal cells. T2-weighted magnetic resonance imaging (T2W-MRI) showed polypoid tumor occupying the entire uterine cavity. The tumor exhibited high signal intensity in diffusion-weighted MRI (DW-MRI) and intense accumulation of 18F-fluorodeoxyglucose (FDG) in positron emission tomography (PET). Intense FDG accumulation was also observed in the left internal iliac region. Total abdominal hysterectomy, bilateral salpingo-oophorectomy, and pelvic lymphadenectomy were performed under the diagnosis of LGESS with lymph node metastasis. However, postoperative histological examination proved that the tumor was ESN without lymph node metastasis. Since mitotic figure is no longer included in the diagnostic criteria of ESN or LGESS, ESN could exhibit high cellularity and high proliferative activity as observed in this case. Therefore, DW-MRI or FDG-PET is not useful in the differentiation of ESN from LGESS.